Predictors of the development of non-cardiogenic syncopal conditions at a young age - D. A. Napalkov; A. A. Sokolova; M. R. Kondratyuk; A. A. Kudryavtseva; P. M. Krupenin; G. E. Savkov; O. D. Savkova; S. Yu. Yagofarova; A. V. Buchneva; J. M. Kwedhi (Кардиоваскулярная терапия и профилактика)
Aim. Syncopal condition in young people are a relatively frequent and poorly understood medical problem. Non-cardiogenic syncope is not sufficiently studied because often they are not raise fears among doctors or patients, and at the same time their causes are associated with many complex medical and diagnostic aspects. The aim of the presented work is to identify the most significant risk factors in the development of non-cardiogenic syncopal conditions, identify triggers and assess the relationship between these factors, the lifestyle and development of syncope.Material and methods. The article presents the results of a descriptive research, including 1031 young people with a history of syncope episodes. The study took into account the presence of chronic diseases which could become a syncope trigger. External triggers (prolonged upright staying, stuffy room, and so on) were also determined.Results. In a multifactor survey of students living in Russia and abroad, the more frequent occurrence of non-cardiogenic syncopal episodes in young girls compared with young men was found. The effect of longterm upright and oxygen corporal were most likely risk factors for syncope.Conclusion. A significant correlation was found between the onset of reflex syncope and the presence of anemia and autonomic dysfunction syndrome. We proved the absence of a correlation between the level of daily load and the frequency of syncope conditions.